Analysis Of Non-B3 Liquid Waste Management In Preventing Environmental Pollution In PT.Kharisma Iskandar Muda Nagan Raya Regency - Cut Ratna Dewi; Dian Fera (Universitas Widya Gama Mahakam Samarinda, 2022)
Background: Non-B3 waste is residual waste from business or industrial activities that do not contain hazardous and toxic materials. This research is based on the Regulation of the Minister of Environment and Forestry of the Republic of Indonesia Number 19 of 2021 concerning Procedures for Management of Non-Hazardous and Toxic Waste from health care facilities. Objectives: This study aims to analyze more deeply related to the Reduction, Storage, Utilization, Stockpiling, and Transboundary Movement of Non-B3 Waste. Research Metodes: This study uses a qualitative method through a descriptive approach with cross-sectional research analysis. Results: From the results of research conducted through interviews, it can be seen that the management of Non-B3 Waste at PT Kharisma Iskandar Muda, Nagan Raya Regency has been carried out in accordance with the regulation of the Minister of Environment and Forestry of the Republic of Indonesia Number 19 of 2021 concerning Procedures for Management of Non-Hazardous and Toxic Waste, which is proven with the cooperation between factory managers in maintaining the cleanliness and health of the environment so that it remains productive and not polluted. Conclusion: Prevention of environmental pollution at PT Kharisma Iskandar Muda is very good, because the factory manager always pays attention to the presence of waste so that it does not spill into the environmental area, in addition PT Kharisma Iskandar Muda also utilizes Non-B3 waste from industrial activities as fertilizer for plantations in the PT. that's on its own